PENGEMBANGAN MODEL PENDUGAAN KELENGASAN LAHAN MENGGUNAKAN DATA MODIS - Domiri, Dede Dirgahayu (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2006)
This research aims to estimate the land moisture condition of the agricultural land, especially for paddy fields based on MODIS (Moderate Resolution Imaging Spectroradiometer) satellite data with 250 m and 500 m spatial resolution and daily temporal resolution. An index called Land Moisture Index (LMI) is created from 1st principle component result of NDSI (Normalize Difference Soil Index), and NDVI (Normalize Difference Vegetation Index), NDWI (Normalize Difference Water Index). There is a high correlation between the LMI and the soil moisture (LM) for the agricultural land with the soil moisture then more 75%, as the increasing of LM is followed by the increasing of the LMI. Based on the above method, the land moisture can be derived spatially from the agricultural land, and especially on the paddy fields for drought prediction.